Numerical Study on the Local Buckling Behaviour of Bolted Steel Plates in Steel Jacketing - Xiao-liang Xu; Zhou-dao Lu; Ling-zhi Li; Chang-jiu Jiang (Advances in Materials Science and Engineering)
A numerical simulation was conducted to investigate the local buckling behaviour of the bolted steel plates in steel jacketing technique. The numerical model was firstly validated by the results of a previous experimental study. Then a parametric study was conducted to investigate the influence of different restraint measures on the local buckling behaviour and the sensitivity of the buckling behaviour to the initial imperfection. Fitted formulae were developed to calculate the structural field capacity of the bolted steel plates, and recommended values of stiffener size were also provided to facilitate the strengthening design of steel jacketing.